Menanggapi Pujian dalam Bahasa Jawa di Semarang - Oktiva Herry Chandra; Marsono Marsono; Suhandano Suhandano (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
Compliment response to a speaker is not a simple task. It often makes speaker in a problematic position among receivers either avoiding disagreement or refraining from implying self-praise. The interesting is that people in every culture background getting involved in this dilema try to find out a way that is able to minimize the potential of making inconvenience by proposing several strategies. The strategies are mainly determined by the culture of the speaker. In Javanese culture, people believe that the good way in establishing relationship with others is being modesty. Javanese have special term for this act, namely andhap ashor. This article aims in explaining the choice of strategies by Javanese. This will reveal the way of Javanese think. The data were collected by the use of observation supported by recording and note-taking technique, and interview. The results shows there are three macro strategies, namely agrreement, nonagreement and request interpretation. These three, then, are broken down into several micro strategies. The choice is based on the obedience to the politeness principles in Javanese circumtances